Assessment of occupational satisfaction of physiotherapists in West Pomeranian Region - Katarzyna Barabasz; Magdalena Gębska; Katarzyna Weber-Nowakowska; Marta Podhorecka; Małgorzata Sielska; Walery Zukow (Kazimierz Wielki University, 2017)
Introduction: The subject of the work is the evaluation of the occupational satisfaction level of physiotherapist. In the available literature, there are few scientific reports assessing the degree of satisfaction of persons performing this profession. The results of the study  show what factors affect the level of occupational satisfaction among physiotherapists. Thanks to the analysis it is possible to eliminate negative factors, which contribute to the increase of dissatisfaction with the work performed. Aim: The main aim was to evaluate the professional satisfaction of physiotherapists in the Zachodniopomorskie voivodship. In addition, the relationship between: the physiotherapist's workplace, their remuneration and the ability to perform new rehabilitation techniques and the level of job satisfaction, and whether or not there are factors influencing the level of job satisfaction. Materials and Methods: The study group consisted of 100 people (74 women, 26 men) aged 22 to 47 years. The respondents are physically active physiotherapists, inhabitants of the West Pomeranian Voivodeship. The study was conducted using the diagnostic survey method and the MSQ Satisfaction Questionnaire (MSQ) was used. Results:The level of professional satisfaction was at a satisfactory level. The main determinants of work were self-fulfillment, self-reliance, ambition and pay. Respondents were less satisfied with working conditions (lack of opportunity for senior management positions and lack of promotion opportunities). The respondents said they were very happy to help others. Conclusions: Professional satisfaction is a key element in the development of a person's attitude towards work. Satisfaction with business and life can only be increased by pointing out and then resolving negative factors.